Origins : the search for our prehistoric past - Rhodes, Frank Harold Trevor (Comstock Publishing Associates, a division of Cornell University Press, 2016)
"Fossils are the fragments from which, piece by laborious piece, the great mosaic of the history of life has been constructed. Here and there, we can supplement these meager scraps by the use of biochemical markers or geochemical signatures that add useful information, but, even with such additional help, our reconstructions and our models of descent are often tentative. For the fossil record is, as we have seen, as biased as it is incomplete. But fragmentary, selective, and biased though it is, the fossil record, with all its imperfections, is still a treasure. Though whole chapters are missing, many pages lost, and the earliest pages so damaged as to be, as yet, virtually unreadable, this--the greatest biography of all--is one in whose closing pages we find ourselves."--OriginsIn Origins, Frank H.T. Rhodes explores the origin and evolution of living things, the changing environments in which they have developed, and the challenges we now face on an increasingly crowded and polluted planet. Rhodes argues that the future well-being of our burgeoning population depends in no small part on our understanding of life's past, its long and slow development, and its intricate interdependencies. Rhodes's accessible and extensively illustrated treatment of the origins narrative describes the nature of the search for prehistoric life, the significance of geologic time, the origin of life, the emergence and spread of flora and fauna, the evolution of primates, and the emergence of modern humans